Comparison of Red Maasai and Dorper sheep for resistance to gastro-intestinal nematode parasites productivity and efficiency in a humid and a semi-arid environment in Kenya - Baker, R.L.; Mugambi, J.M.M.; Audho, James O.; Carles, A.B.; Thorpe, W.R. (INRA, 2002)
Disease resistance/tolerance, productivity and efficiency of Red Massai and Dorper sheep evaluated in experiments at the Kenya coast (humid environment) and the Kenya highlands (Semi-arid environment). There were important breed by location interactions for LWT, mortality rates and reproduction rates. When all these parameters were combined it was found more productive and efficient than Dorper sheep in humid coastal environment. In the semi-arid environment Dorper sheep were slightly more productive than the Red Maasai, but there was no significant difference in Flock efficiency between the breeds.